Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres